(3eNJUQ GdCZGfj dCHj GdaQL GdCUHgGfjs - (3SdjeGf Hf eMeO Hf YHO Gddg Hf ESeGYjd, CHh GdQHjY, GdTQja GdYdhqj ,Gdnerhdj oSndjeGf,J (B1238 (3g`s ((3eQGcT s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GddhM hGdbde CHhbWjaI GdeYjWj(B: (3gh YeQh Hf GdhdjO Hf YbHI Hf CHj eYjW s
(3BNQgG (B:s
(3CYQaJ QSekG ef oSejg HGddhi OQLJ Ydjg GdQjM HYOc aGSJhi ced GdSaQ GdChd jJdhg aj GdSaQ GdKGfj TYQ GHf YQjV s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JUMjMGJ hJYdjbGJ LjOIs
(3hHChdgG CSeGA GdTYQGA GdeJQLe dges
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs